(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: Find out the status of adherence to treatment of children with drug-resistant epilepsy and several factors related to treatment at Nghe An Obstetrics and Pediatrics Hospital. Subjects-methods: Cross-sectional description all pediatric patients diagnosed with drug-resistant epilepsy according to WHO criteria and primary caregivers at Nghe An Obstetrics and Pediatrics Hospital. Result: There were 75 children who met the research criteria. 47.8% of children are in the 1-5 age group, 91.1% of parents are direct carers. The education level of caregivers from high school or higher is 68.0%. The child’s history had 24% of febrile convulsions. The duration of treatment for epilepsy lasted for the majority of patients over 2 years 60%. The number of patients with good adherence to treatment accounted for 84%. Finding a statistically significant relationship between caregiver education and adherence (p < 0.05). Conclusions: The percentage of patients who complied with treatment and re-examination is quite high. Factor that was statistically significant for children’s compliance is caregiver’s education level.